FAKTOR YANG MEMPENGARUHI IMPLEMENTASI PERATURAN DAERAH TENTANG TARIF PARKIR TEPI JALAN DI KOTA PAREPARE - Ruslang T; Kurniawan Saputra; Dayu Suhardi; Bahruddin Bahruddin; Fajar Ladung (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2026)
This study aims to analyze the factors influencing the implementation of regional regulations on roadside parking tariff imposition in Parepare City. A qualitative approach with a case study method was employed in this research. The informants comprised the Secretary of the Transportation Agency of Parepare City, the Head of the Parking Technical Implementation Unit (UPTD), and five parking attendants from different locations. Data collection was conducted through observation, in-depth interviews, and documentation. Data analysis utilized the interactive model of Miles and Huberman, encompassing data reduction, data display, and conclusion drawing. The findings reveal that two primary factors influence parking policy implementation: Content of Policy and Context of Implementation. Among six Content of Policy indicators, Program Implementer and Resources Committed were identified as the most influential factors requiring significant improvement. The lack of technical regulations and insufficient human resources for supervision constitute the main obstacles to achieving parking retribution targets, which have only reached an average of 55.85% over the past four years. Meanwhile, all three Context of Implementation indicators have generally provided positive support for the implementation of regional government policies. This research contributes to the understanding of policy implementation challenges in local revenue management and provides practical recommendations for improving roadside parking governance in Parepare City.